The Role of Dectin-1-Mediated M1 Macrophage Polarization in Cerebral Ischemia-Reperfusion Injury - Chen Zongyun; Lin Bixia; Ding Fadian; Hong Xiaoping; Chen Hongbin; Deng Yu; Liu Qicai; Ye Xiaoyi; Zeng Kai (Emergency Medicine International)
Introduction. The advances in cerebral ischemia treatment have resulted in a larger proportion of patients get the benefits of rebuilding blood flow to the brain. Then, ischemia-reperfusion injury has emerged as a new essential problem. Dectin-1 plays an important role in cerebral ischemia-reperfusion injury by regulating the function of immune cells. Methods. C57BL/6 was blindly divided into four groups including the sham-operated group and the three different kinds of middle cerebral artery occlusion (MCAO) groups (after 6 hours, 12 hours, and 24 hours after plug removal). The protein expression levels of dectin-1, proapoptosis molecule, and antiapoptosis molecule were measured by using western blot analysis. The brain tissue was analyzed by flow cytometry to detect the M1 macrophage levels. Results. The correlation analysis of dectin-1 and infarct areas showed that there was an obviously positive correlation in between them (R = 0.9603). Dectin-1, cleaved caspase-3, and Bax increased, while antiapoptosis molecule, Bcl-2, decreased at three appropriate time points (after 6 hours, 12 hours, and 24 hours). The level of M1 macrophages in the experimental group increased after ischemia-reperfusion injury compared to the control group. Conclusions. The high expression level of dectin-1 may affect M1 macrophage polarization and brain cell apoptosis in cerebral ischemia-reperfusion injury.